Examining the relationship between ecological anxiety and pro-environmental behavior: personal and collective actions - Carasso Romano, Gal Hagit; Sippori, Rotem; Soroker, Sharon (Frontiers in Psychology, 2025)
Ecological anxiety—defined as anxiety related to environmental degradation and climate change—has become increasingly prevalent, particularly among individuals who are environmentally conscious. This study investigated the correlation between ecological anxiety and both personal and collective pro-environmental behavior among 224 participants, predominantly members of environmental groups with inherent environmental concern. The study aimed to clarify the extent to which ecological anxiety motivates different forms of environmental behavior, and whether personal and collective actions serve similar psychological functions. Using Pearson’s correlation and regression analysis, the research identified significant positive correlations between ecological anxiety and both forms of environmental behavior, with a notably stronger correlation for collective behavior. The study also examined whether environmental actions serve as coping mechanisms that provide individuals with a sense of control over uncontrollable environmental situations, or alternatively, whether these actions could exacerbate anxiety among those actively engaged in addressing environmental challenges. These findings are particularly relevant for mental health professionals, environmental educators, and policymakers, as they emphasize the need to consider both personal and collective dimensions of environmental behavior. Integrating this perspective into educational programs and policy design may help transform ecological anxiety into a constructive force for environmental engagement and resilience.